Anemia ferropénica como factor de riesgo para ansiedad y/o depresión en niños de 8 a 13 años del servicio de pediatría del Hospital Víctor Lazarte Echegaray, Enero 2020 - Diciembre 2020 - Incio Onolasco, Georcy Jacqueline (2020)
Currently, mental illness in children and adolescents is on the rise. Anxiety and depression are the most prevalent. On the other hand, anemia, which affects approximately one third of the world's population, has been linked to certain mental disorders. The objective of this project is to demonstrate whether iron deficiency anemia is a risk factor for anxiety and/or depression in children. Thus, if the proposed association is demonstrated, a new reason to avoid and prevent iron deficiency anemia could be identified and will contribute to generate an approach for health authorities to develop better prevention and health promotion strategies.